Pembinaan dan Pendampingan Pimpinanan Keperawatan dalam Melaksanakan Peran dan Fungsi Manajemen pada Kepala Ruang di RS PKU Muhammadiyah Surakarta - Pratiw, Arumi; Utami, Yuni Wulan (Universitas Muhammadiyah Surakarta, 2010)
Role and function management must be done nurse manager in hospital. Nursing lowmanager one of leader which conduct the leadership role and function. The aim ofthe activity is improving duty of nurse low manager when they conducted leadershiprole and function. The participate in the activity are nurse low manager and primarynursing. The method of activity are lecturer, discusion, simulation and demonstration.The result of activity describe improving level of knowledge nurse low manager. Inaddition, nurse low manage